Android-Based E-Commerce Implementation as an Innovation in Restaurant Entrepreneurship in the Selayar Archipelago - M. Salim; Sulistiawati R.N Ahmad (IECON: International Economics and Business Conference, 2024)
This research has explored how Android-based e-commerce is used for catering entrepreneurship in Selayaran Archipelago. The project seeks to build an e-commerce platform that will alter the balance of power in the region's restaurants, utilizing the electronic medium for improving local food businesses and promoting sustainable economic development. With the accelerated growth of applications for local food delivery, mistakes abound in how local food businesses attempt to expand frontiers and remedying internal efficiency failings. One uses the Research and Development (R&D) method to work out needs analysis, design, development and system test in different Selayarautlay restaurants. Interviews and surveys were carried out in Selayar among restaurant owners and customers involved with eating out, so that we might understand the problems and opportunities of applying digital hardware. The results indicate that the Android-based e-commerce platform positively contributes to business growth by increasing visibility, reducing transaction times, and enabling more personalized customer interactions. This implementation offers valuable insights into digital transformation for small to medium-sized restaurant businesses in rural areas, providing a model that supports local entrepreneurship through technological innovation. The findings suggest that developing e-commerce capabilities in the restaurant sector can not only improve service quality and customer satisfaction but also create a sustainable model for local economic growth in the Selayar Archipelago.